2018
DOI: 10.1021/acsami.7b19498
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Ultrasmall Manganese-Doped Multimetallic Oxysulfide Nanoparticles as Highly Efficient Oxygen Reduction Electrocatalyst

Abstract: The highly efficient and cheap non-Pt-based electrocatalysts such as transition-based catalysts prepared via facile methods for oxygen reduction reaction (ORR) are desirable for large-scale practical industry applications in energy conversion and storage systems. Herein, we report a straightforward top-down synthesis of monodisperse ultrasmall manganese-doped multimetallic (ZnGe) oxysulfide nanoparticles (NPs) as an efficient ORR electrocatalyst by simple ultrasonic treatment of the Mn-doped Zn-Ge-S chalcogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 102 publications
2
21
0
Order By: Relevance
“…[27][28][29][30][31][32] Recently, discrete clusters with uniform size and atomically precise crystal lattice structure have been successfully dispersed into cluster-based quantum-dotlike nanoparticles (also called supraclusters) in solvents, and correlations between the cluster structure and function (such as electrochemical, photocatalytic and photoelectric applications) have been established. [33][34][35][36][37] Although the roles of clusters in crystalline open frameworks remain unclear, the signicance of clusters in these frameworks seems to extend beyond the beauty of a symmetrical structure and apparent functionality as nodes for open framework construction. For example, precise doping of clusters at the atomic scale allows one to study the synergistic effect of framework heteroatoms on photoluminescence and electrocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32] Recently, discrete clusters with uniform size and atomically precise crystal lattice structure have been successfully dispersed into cluster-based quantum-dotlike nanoparticles (also called supraclusters) in solvents, and correlations between the cluster structure and function (such as electrochemical, photocatalytic and photoelectric applications) have been established. [33][34][35][36][37] Although the roles of clusters in crystalline open frameworks remain unclear, the signicance of clusters in these frameworks seems to extend beyond the beauty of a symmetrical structure and apparent functionality as nodes for open framework construction. For example, precise doping of clusters at the atomic scale allows one to study the synergistic effect of framework heteroatoms on photoluminescence and electrocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wide range of TM compounds with oxysulfides, e.g., (CoNi)O x S y , Si-MWs@MoO x S y , CoO 0.87 S 0.13 /GN, Ni y Co 1−y O x S z , and Mn(Zn, Ge) oxysulfide [8,130,131], have been explored as a catalyst for electrochemical applications such as supercapacitors [132], PEC [130], Zn-air batteries [133], PEMWE [134] and ORR [135]. Subsequently, Suntivich's group investigated a partial S anionic substitution in CoO NPs to increase the H 2 evolution [50].…”
Section: Oxysulfidementioning
confidence: 99%
“…The O and S derived from the same VIA group of the periodic table are easily mixed to modify the compounds. To date, a wide range of TM compounds with oxysulfides, e.g., (CoNi)O x S y , Si-MWs@MoO x S y , CoO 0.87 S 0.13 /GN, Ni y Co 1− y O x S z , and Mn(Zn, Ge) oxysulfide [ 8 , 130 , 131 ], have been explored as a catalyst for electrochemical applications such as supercapacitors [ 132 ], PEC [ 130 ], Zn-air batteries [ 133 ], PEMWE [ 134 ] and ORR [ 135 ].…”
Section: Electrocatalytic Performance Of Anion-mixed Electrocatalystsmentioning
confidence: 99%
“…In order to fabricate functional nanomaterials, e.g., for optoelectronic devices, by processing such supertetrahedral clusters, there has been an increasing interest in dissolving such materials in common solvents. 19 However, only a few studies about dissolving ligand-free clusters have been reported, and most of them required the use of highly polar solvents like water or methanol owing to the relatively strong electrostatic interactions between anionic clusters and cationic counterions. 20 Therefore, it is significant and at the same time challenging to alleviate the above-mentioned electrostatic interactions, for a corresponding extension of the applications of materials based on supertetrahedral chalcogenido (semi)metalate units.…”
Section: Introductionmentioning
confidence: 99%